2020
DOI: 10.1097/nmd.0000000000001209
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among Delayed Sleep Phase Disorder, Emotional Dysregulation, and Affective Temperaments in Adults With Attention Deficit Hyperactivity Disorder and Cyclothymia

Abstract: This study aims to explore the relationships between Delayed Sleep Phase Disorder (DSPD) and emotional dysregulation in 240 patients (134 with cyclothymia, 81 with ADHD and 25 with both conditions). DSPD was assessed using the Morningness-Eveningness Questionnaire, followed by a clinical evaluation. Affective temperaments and emotional dysregulation were also investigated through BriefTEMPS-M and RIPoSt questionnaires respectively. Clinical variables were compared in patients with and without DSPD and a logist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…This would make it possible to set up early interventions with children with ADHD and investigate the impact on ADHD symptomatology, eating behaviors and risk of obesity in adolescence and adulthood. An important area of research would be to focus on the interplay between dysregulation of sleep, weight gain and emotional dysregulation, as it has been suggested by some authors [145] that alterations in sleep/arousal may be related to ADHD and weight gain/disordered eating and sleep deprivation may exacerbate emotional dysregulation [146].…”
Section: Discussionmentioning
confidence: 99%
“…This would make it possible to set up early interventions with children with ADHD and investigate the impact on ADHD symptomatology, eating behaviors and risk of obesity in adolescence and adulthood. An important area of research would be to focus on the interplay between dysregulation of sleep, weight gain and emotional dysregulation, as it has been suggested by some authors [145] that alterations in sleep/arousal may be related to ADHD and weight gain/disordered eating and sleep deprivation may exacerbate emotional dysregulation [146].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the only study which has directly assessed the relationship between affective temperaments and impulsivity was carried out in a non-clinical sample and found that cyclothymic disposition was strongly correlated with high levels of impulsivity and pathological gambling [ 2 ]. The lack of evidence on this association is surprising, since some affective dispositions, such as irritable and cyclothymic temperaments, and trait-related impulsivity, have several elements in common, including mood instability and reactivity [ 71 ], reduced cognitive performance under stressful situations, a higher recurrence of aggressive behaviors and substance abuse [ 36 ], and emotional dysregulation [ 72 , 73 ], with important therapeutic and prognostic implications. These common characteristics were confirmed by our finding of the association of cyclothymic and irritable temperaments with trait-related impulsivity.…”
Section: Discussionmentioning
confidence: 99%
“…As for the influence of affective temperaments on suicidal ideation, cyclothymic and depressive affective temperaments were found to be higher in individuals with prominent psychological distress and this effect was mediated by the lack of impulse control and lack of clarity dimensions of emotional dysregulation [ 38 ]. In another study, the cyclothymic temperament was found to be predisposed to the consequences of emotional dysregulation in an attention deficit/hyperactivity disorder [ 39 ]. Emotional dysregulation in turn was found to moderate the link between mental pain and suicidal ideation [ 40 ].…”
Section: Discussionmentioning
confidence: 99%